Fenomena struktur modal di Indonesia - Axel Giovanni; Devi Wahyu Utami; Ibnu Nur Hamzah (Jurnal Manajemen Indonesia, 2022)
This study aims to provide empirical evidence regarding the capital structure phenomenon in non-financial sector companies in Indonesia. The study population was all non-financial companies listed on the Indonesia Stock Exchange for the 2014-2018 period. The research sample of 1,770 companies obtained through the purposive sampling method. This research uses descriptive study method. The result of this study show that the basic industry and chemical sectors have the highest average use of debt than other non-financial sectors in the 2014-2018 period. Meanwhile, the consumer goods industry is the non-financial sector, with the lowest average debt utilization level in the 2014-2018 period. This study sees that, in general, the company's capital structure changes with changes in macroeconomic conditions. Keywords— Capital structure; descriptive study; phenomenon